Enhancing Psychiatric Competence: A Simulation-Based Approach to Improving Medical Students’ Knowledge and Confidence - Iqra Saani (BJPsych Open)
Aims: Psychiatry is often considered a challenging specialty by medical students, largely due to the stigma attached to it. It also demands a unique skill set and relies heavily on interpreting subjective experiences, which can be a daunting task. Many students report hesitancy when approaching psychiatric patients, which indicates a need to bridge the gap between theoretical and practical learning. We believe that simulation is an effective way to achieve this. The aim of this Quality Improvement Project (QIP) was to assess and enhance medical students’ knowledge and understanding of common psychiatric conditions and instil confidence in them regarding psychiatric evaluation.